Closure modeling in reduced-order model of Burgers' equation for control applications. (March 2017) - Imtiaz, Haroon; Akhtar, Imran
A proper orthogonal decomposition (POD) technique has been successfully employed to develop reduced-order models for flow control purposes. For complex flows, higher POD modes also play a significant role in the stability and accuracy of the reduced-order model, thus require a closure, as in turbulent flows. In the presence of nonhomogeneous boundary conditions, developing a closure model becomes a challenging task. This paper discusses nonlinear closure modeling approaches for homogeneous and nonhomogeneous boundary conditions. Burgers' equations, both one-dimensional and two-dimensional, are considered as the governing equations to develop reduced-order models with different boundary conditions. Homogeneous and nonhomogeneous boundary conditions are considered to demonstrate the effectiveness of the proposed closure modeling technique in boundary control applications. Numerical results show that the proposed closure model improves the accuracy of the reduced-order model.